Expanding Disease Spectrum Associated With Puerperal Mastitis - Gregg L. McAdoo; Gilles R. G. Monif (Hindawi Limited, 1997)
Background: Staphylococcus aureus and the β-hemolytic streptococci are the commonest causes of puerperal mastitis which tends to be a localized disease process. This report describes 2 cases attributable to these bacteria that resulted in extramammary involvement and augmented morbidity.